Analysis of the Role of Government in Eradicating Corruption in Indonesia - Muhamad Izwan Aiman; Bagus Rofiqul Faradiis; Faisal Ariq Athalullah Misbahul Islam (SS&H: Studies in Social Sciences and Humanities, 2025)
Corruption in Indonesia is a major challenge that affects many aspects of life, including economic, social and public trust in the government. government. This research aims to analyze the government's role in eradicating corruption with a systematic approach to related literature. The study highlights the importance of bureaucratic reform, increased information disclosure, and collaboration between law enforcement agencies. information, as well as collaboration between law enforcement agencies, such as the KPK, Police, and Prosecutors' Office. The research shows that despite increased strategic efforts in the fight against corruption, challenges in the form of political intervention and resistance from certain parties remain the main obstacles. playing obstacles. The active participation of the public, especially the younger generation, and the use of digital technology have also proven to play an important role in the fight against corruption. use of digital technology has also proven to play an important role in public scrutiny and reporting of corruption cases. With stronger synergy between the government, the public, and the media, it is hoped that efforts to eradicate corruption can be more effective in building a clean, transparent and accountable government.